A synergetic strategy of well dispersing hydrophilic Ti3C2Tx MXene into hydrophobic polybenzoxazine composites for improved comprehensive performances. (1st March 2022) - Liu, Jingkai; Jia, Xichen; Liu, Yuan; Wuliu, Yishun; Dai, Jinyue; Zhu, Xinbei; Liu, Xiaoqing
Abstract: The uniform distribution of hydrophilic two-dimensional nanosheets in hydrophobic polymeric matrix and strong interfacial interaction between them are of great significance for the fabrication of composites, but challenging. In this work, an easily-operating strategy to prepare Ti3 C2 Tx MXene/polybenzoxazine (PBZ) composites with homogeneous dispersion and enhanced comprehensive properties is reported, in which the rich polar groups on MXene surface and purposefully constructed hydrogen bonds (H-bonds) play crucial roles. Specifically, the oxygen and fluorine-containing terminations on Ti3 C2 Tx MXene surface were increased by varied etching conditions. Then, the composites were prepared by solvent-assisted drop-casting and annealing method. The H-bonds between MXene and benzoxazine can not only accelerate the ring-opening polymerization, but also enhance their interfacial interactions. Accordingly, the obtained composites exhibited excellent comprehensive properties, showing the enhancement in tensile strength of 22.1%, impact strength of 50%, and thermal conductivity of 67.3% when the filler content was only 2 wt%. This study provides us a H-bonds assisted method to disperse hydrophilic nanosheets in hydrophobic polymeric matrix for the fabrication of nanocomposites with enhanced properties.